Bio‐Based Polyketones by Selective Ring‐Opening Radical Polymerization of α‐Pinene‐Derived Pinocarvone. (11th December 2015) - Miyaji, Hisanari; Satoh, Kotaro; Kamigaito, Masami
Abstract: The most abundant naturally occurring terpene, α‐pinene, which cannot be directly polymerized into high polymers by any polymerization method, was quantitatively converted under visible‐light irradiation into pinocarvone, which possesses a reactive exo methylene group. The bicyclic vinyl ketone was quantitatively polymerized in fluoroalcohols by selective (99 %) ring‐opening radical polymerization of the four‐membered ring, which results in unique polymers containing chiral six‐membered rings with conjugated ketone units in the main chain. These polymers display good thermal properties, optical activities, and contain reactive conjugated ketone units. Reversible addition fragmentation chain transfer (RAFT) polymerization was successfully accomplished by using appropriate trithiocarbonate RAFT agents, enabling the synthesis of thermoplastic elastomers based on controlled macromolecular architectures.